Effect of Phosphating Temperature on Surface Properties of Manganese Phosphate Coating on HSLA Steel - Jana Pastorkova; Martina Jackova; Filip Pastorek; Zuzana Florkova; Juliana Drabikova (Communications - Scientific letters of the University of Zilina, 2020)
A phosphating process modified for a high-strength low-alloy (HSLA) steel was performed at various temperatures and influence on the surface properties of the Domex steel covered by manganese phosphate (MnP) was investigated by electrochemical corrosion tests supported by a photo documentation performed by the SEM. Corrosion measurements were performed in 0.1M NaCl solution at 22±2 °C using electrochemical impedance spectroscopy and potentio-dynamic polarisation in order to obtain thermodynamic and kinetic corrosion characteristics and individual elements of equivalent circuits. It is that a temperature of the phosphating process has a very significant effect on protection properties of the created manganese phosphate coating on the Domex steel and needs to be strictly monitored. According to results of corrosion testing and surface morphology observations, the optimal temperature for the phosphating process on the tested Domex steel was chosen.